Accidental swallowing of dentures: case report and literature review - Hussain, Tanvir; Slattery, Fionn; Munir, Javid (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2022)
Unintentional ingestion of dentures is relatively common. Several factors have been implicated in increasing the risk of accidental denture swallowing including neurological impairments, dementia, cerebral hemorrhage, intoxication, and learning difficulties. This paper will aim to discuss a case and review the literature on accidental ingestion of dentures. The paper involved reviewing a case of accidental denture ingestion by a 34-year-old male patient. The patient ingested his dentures while eating ice cream. He displayed no signs of respiratory distress and reported difficulty ingesting solids, nausea, and a feeling of something lodged in his throat. X-rays revealed an increase in the anteroposterior diameter prevertebral space. The dentures were removed by direct laryngoscopy with the aid of optical foreign body removal forceps. The case and the literature review revealed that denture ingestion can occur when engaging in high-risk activities such as falls, eating, anesthesia, drinking, and sleeping. The site of denture impaction determines the signs and symptoms that the patient will present. Complications associated with denture impaction may include necrosis, bleeding, perforation, and obstruction. Assessing the patient involves considering psycho-neurological deficits, the possibility of mental health problems, oral assessment, the nature and dimensions of the ingested denture, and the presence of complications. Treatment typically involves wait-and-watch, endoscopy, or surgery. Accidental ingestion of dentures can constitute a medical or airway emergency that should be managed promptly. The management of such patients should involve considerations of the site of ingestion and the possibility of complications.